A phase 2, multicenter, double-blind, randomized, vehicle-controlled clinical study to compare the safety and efficacy of a halobetasol propionate 0.01% lotion and halobetasol propionate 0.05% cream in the treatment of plaque psoriasis. (19th May 2019) - Kerdel, Francisco A.; Draelos, Zoe D.; Tyring, Stephen K.; Lin, Tina; Pillai, Radhakrishnan
Abstract: Background: Halobetasol propionate (HP) 0.05% is a highly effective short-term treatment for plaque psoriasis. Objective: Compare efficacy and safety of once-daily HP 0.01% lotion and 0.05% cream (Ultravate ® ) in moderate-to-severe psoriasis. Methods: Multicenter, randomized, double-blind, vehicle-controlled Phase 2 study ( N  = 150). Patients randomized to HP 0.01% lotion, HP 0.05% cream, or vehicle, once-daily for 2 weeks. Efficacy assessments included treatment success; impact on erythema, plaque elevation, and scaling; and improvement in body surface area (BSA). Safety and treatment-emergent adverse events (TEAEs) were evaluated throughout. Results: 30.0% and 31.6% of patients were treatment successes with HP 0.01% lotion and HP 0.05% cream ( p  = .854). A 2-grade improvement in erythema, plaque elevation and scaling was achieved in 38.3%, 40.0%, and 43.3% of patients, compared with 31.6% ( p  = .446), 36.8% ( p  = .727), and 47.4% ( p  = .663) on HP 0.05% cream. BSA improved by 22.3% with HP 0.01% lotion compared with 20.9% ( p  = .787). There was one treatment-related application-site reaction with HP 0.01% lotion, and no AE reports of skin atrophy, striae, telangiectasia, or folliculitis. Conclusions: Halobetasol propionate 0.01% lotion was comparable to the higher concentration halobetasol propionate 0.05% cream; achieving treatment success, reducing psoriasis signs at the target lesion, and improving BSA following two weeks' daily-treatment. Both treatments were well-tolerated. Clinical Trials Registration: clinicaltrials.gov NCT02785185